Предмет: Математика,
автор: bmwtop56678
Спростіть вираз: (3x²-2x)+(-x2 + 3x); (4c² -2cd)-(10c²+8cd); помогите пжпжпжпдпд
Ответы
Автор ответа:
2
Ответ: 1) 2х² + х; 2) -6c² - 10cd.
Пошаговое объяснение:
1) (3x² - 2x) + (-x² + 3x) = 3х² - 2х - х² + 3х = 2х² + х;
2) (4c² - 2cd) - (10c² + 8cd) = 4с² - 2сd - 10c² - 8cd = -6c² - 10cd.
bmwtop56678:
спасибо, помог
Похожие вопросы
Предмет: Алгебра,
автор: EgorSasenow
Предмет: Литература,
автор: star7778
Предмет: История,
автор: annarichter
Предмет: Русский язык,
автор: rtshhsysuwuw